Reading the canon: literary history in the 21st century - Löffler, Philipp (American studies, 2017)
Introduction: The practices of reading and the need for literary value / Philipp Löffler -- Literary history and the problem of periodization / Clemens Spahr -- Singularity and the literary market / Günter Leypoldt -- Literary value and the question of generic change / Michael Basseler -- Shakespeare's complete works : canonization, completion, and collection in the 21st century / Peter Paul Schnierer -- The uses of Emerson : transcendentalism, transnationalism, and the New Americanists / Johannes Volz -- Edgar Allan Poe and the rise of detective fiction / Heiko Jakubzik -- Canon fodder : Thomas Pynchon and the invention of postmodernism / Sascha Pöhlmann -- Sherman Alexie and the uses of Native American literature / Franziska Schmid -- African-American literature, canonization, and the Nobel Prize : German and American perspectives on Toni Morrison / Katharina Gerund -- Canon and carnival : challenging hierarchies in Zadie Smith's NW / Caroline Lusin -- New canons in the classroom : teaching Black British writing / Jan Rupp -- The great unread : the shadow canon of Indian writing in English / Dirk Wiemann -- John Neal and the problem of Romanticism / Stefanie Schäfer -- Only in the chattel records : obscurity, historiography, and Frederick Douglass' The heroic slave / Karin Höpker -- Charismatic authorship : Walter Scott, William Wordsworth, and the nineteenth-century construction of Romantic canonicity / Tim Sommer -- No longer the text-book of any generation : Stover at Yale and the non-canonical / Sophie Spieler -- Highbrow - Middlebrow - Broadbrow? J. B. Priestley and cultural re-education in postwar Germany / Kirsten Hertel -- Canonizing youth in Mark Ravenhill's plays / Ellen Redling
Literaturangaben
Keywords: Aufsatzsammlung; Gattungstheorie; Periodisierung; Kanon; Literatur; USA